Influence of geometry and fiber properties on rupture strain of cylindrical FRP jackets under internal ICE pressure. (15th May 2018) - Sadeghian, Pedram; Seracino, Rudolf; Das, Baishali; Lucier, Gregory
Abstract: This paper presents an study on the rupture strain of cylindrical fiber-reinforced polymer (FRP) jackets under internal ice pressure. A total of 45 cylindrical FRP jackets were prepared using three unidirectional carbon, glass, and basalt fabrics in three different internal diameters, namely 60, 114, and 216 mm, and one-, two-, and three-plies. Three jackets for each combination were typically tested and the average hoop rupture strains were obtained and compared to the rupture strain of flat coupons in the form of a strain efficiency factor. It was found that the strain efficiency factor ranged from 0.53 to 1.05 with an average of 0.77. A new analytical model was also developed based on the bi-axial state of stress in a cylindrical FRP jacket to obtain the rupture strain and strain efficiency factor of the FRP jacket using a closed-form solution. The model engaged four major parameters, namely: diameter, thickness, axial/transverse strength ratio, and Poisson's ratio of the FRP jacket. The two latter parameters were eliminated after a parametric study to propose a simplified formula. The analytical and simplified models predicted the experimental strain efficiency factors with an average error of −3.4% and −4.6%, respectively.